Degradation of limestone exposed to drying and wetting cycles experimental study - Al-Bared, A. M. (2020)
Degradation of rock is the deterioration of the rock forming materials and the reduction of strength and stiffness within time. It is responsible for the failure of rock slopes and landslides as the drying and wetting cycles in long-term will extensively reduce the strength of the rock and eventually end up as a soil-like material. Weathering rate is very crucial, and it is the main parameter inducing and accelerating degradation of rock. This study focuses on investigating and evaluating the effect of degradation on cored samples of limestone. Limestone was collected from the state of Perak, Malaysia and the samples were cored, trimmed and cut into 50 mm diameter and 80 mm height. A total number of 30 samples were exposed to different number of drying and wetting cycles in the laboratory. A total number of 27samples were tested using the Uniaxial compression test after 0 - 14 cycles while three samples were exposed to exactly 14 cycles to observe the reduction in weight. The results showed the strength of limestone to decrease gradually with the increment of drying and wetting cycles. Besides, samples that were continuously exposed to 14 drying and wetting cycles experienced a weight reduction of approximately 1.12%.